Synthesis of Novel Tadalafil Analogues and their Evaluation as Phosphodiesterase Inhibitors and Anticancer Agents - Ashraf H, Abadi; Dalal A, Abouel-Ella; Nermin S, Ahmed; Bernard D, Gary; Jose T, Thaiparambil; Heather N, Tinsley; Adam B, Keeton; Gary A, Piazza (Arzneimittelforschung, 2009)
Two closely related series of novel β-car-boline derivatives, electronically similar to tadalafil (CAS 171596-29-5), were synthesized and evaluated for their inhibitory effects upon phosphodiesterase 5 (PDE5) and phosphodiesterase 11 (PDE11) and their in vitro tumor cell growth inhibitory activity versus HT29 colorectal carcinoma cell line. Interestingly, some of the synthesized compounds showed growth inhibitory properties that appear to be associated with their ability to inhibit PDE5. Moreover, the PDE5 inhibition seems relevant to the stereochemical aspects of the compounds.
Keywords: Antitumor agents; ß-Carboline derivatives, anticancer activity, phosphodiesterase 5 inhibition; CAS 171596-29-5; Tadalafil